26 Testosterone (T) Challenge in Men Post-Radical Prostatectomy (RP) with Profoundly Low Testosterone. Issue 1 (1st April 2022) - Flores Martinez, J; Mulhall, JP; Deveci, S; Matsushita, K; Torremade, J; Salter, CA
ABSTRACT: Introduction: Prostate specific antigen is the primary marker of prostate cancer recurrence. PSA secretion is T dependent with T levels below saturation point associated with sub-optimal PSA production. Men with an undetectable PSA level after RP with very low T levels might have an artificially low PSA level. Objective: We aimed to evaluate the effects of raising T level in such men. Methods: Study population consisted of (i) men post-RP (ii) with undetectable PSA level (iii) total T levels <200 ng/dl (two levels, LCMS) who (iv) underwent in-office intramuscular injection of 100mg of T cypionate (v) had a PSA level checked 5 days later, and if undetectable every month after that, 3 months later then every 6 months and (vi) follow-up of at least 24 months on T therapy. Results: 22 men have been challenged thus far. Mean age 62±18 years. Mean preoperative PSA 6.2. Mean post-RP TT value 140± 35 ng/dL 2.2. Median Gleason sum 7. 23% had GS ≥8. Mean post-RP, pre-challenge T value 140± 35 ng/dL. Mean time post-RP to challenge was 7± 9 months. Mean TT value 5 days after IMT challenge 640± 220 ng/dL, all with TT levels above 400. 5/22 has a PSA elevation, 2 immediately after IMT challenge (PSA values 0.07, 0.08). All other men started T therapy immediately and had PSA elevation at 9, 14 and 22 months after commencing T therapy (PSA values 0.08, 0.12, 0.11). All patients with PSA elevation had continued rise in PSA and had detectable disease on imaging. All men with PSA recurrence had either GS 7 with unfavorable pathology (2) or GS ≥8 (3). Conclusions: This T challenge approach permits the early detection of prostate cancer recurrence permitting early intervention. About 10% of such men had a PSA rise immediately after T challenge. Disclosure: No